Patients with systemic lupus erythematosus have abnormally elevated Epstein–Barr virus load in blood - Moon, Uk Yeol (BioMed Central, 2004)
Various genetic and environmental factors appear to be involved in systemic lupus erythematosus (SLE). Epstein–Barr virus (EBV) is among the environmental factors that are suspected of predisposing to SLE, based on the characteristics of EBV itself and on sequence homologies between autoantigens and EBV antigens. In addition, higher titers of anti-EBV antibodies and increased EBV seroconversion rates have been observed in SLE patients as compared with healthy control individuals. Serologic responses do not directly reflect EBV status within the body. Clarification of the precise status of EBV infection in SLE patients would help to improve our understanding of the role played by EBV in this disease. In the present study we determined EBV types in SLE patients (n = 66) and normal control individual (n = 63) by direct PCR analysis of mouthwash samples. We also compared EBV load in blood between SLE patients (n = 24) and healthy control individuals (n = 29) using semiquantitative PCR assay. The number of infections and EBV type distribution were similar between adult SLE patients and healthy control individuals (98.5% versus 94%). Interestingly, the EBV burden in peripheral blood mononuclear cells (PBMCs) was over 15-fold greater in SLE patients than in healthy control individuals (mean ± standard deviation: 463 ± 570 EBV genome copies/3 μg PBMC DNA versus 30 ± 29 EBV genome copies/3 μg PBMC DNA; P = 0.001), suggesting that EBV infection is abnormally regulated in SLE. The abnormally increased proportion of EBV-infected B cells in the SLE patients may contribute to enhanced autoantibody production in this disease.